Source apportionment of PM2.5 pollution in the central six districts of Beijing, China. (10th February 2018) - Zhang, Yuepeng; Li, Xuan; Nie, Teng; Qi, Jun; Chen, Jing; Wu, Qiong
Abstract: Fine particulate matter (PM2.5 ) has become the primary atmospheric pollutant in Beijing in recent years, causing widespread concern in society. Understanding the origin of PM2.5 is essential for developing effective strategies to reduce PM2.5 . In this study, we used the Particulate Matter Source Apportionment Technology (PSAT) in Comprehensive Air Quality Model with Extensions (CAMx) to quantify the contributions of different source regions and emission categories to the PM2.5 concentration in the central six districts of Beijing in January, April, July and October, representing four seasons in 2014. The annual contribution ratios from local, suburb and the surrounding regions of Beijing as well as the outside of boundary region were 47.6, 19.3, 11.4, and 21.7%, respectively, showing significant contribution of regional transport to the PM2.5 pollution in the central six districts of Beijing. The emission category apportionment results in the central six districts showed distinct seasonal variations with important contribution of coal combustion in winter but minor contribution in the other seasons, dominant contribution of dust in spring, and dominant contribution of the vehicle related sources in the other seasons. Moreover, the detailed contribution proportion of the five emission categories showed clear spatial variation in the suburbs and the surrounding regions. Based on the sensitivity analysis of local emission reduction, the control of the vehicle related sources was the most efficient mitigation measure for the reduction of PM2.5 during the case study period in autumn, but the efficiency of the local mitigation measures was greatly reduced in the period of heavy PM2.5 pollution.